Christian Involvement in Politics: Presuppositions and Resources - Christopher Duraisingh, (Journal of Dharma, 1982)
Underlying this presentation is the conviction that being a Chris- tian implies being involved in politics. Politics is understood herein as the process of structuring the conduct, rights and responsibilities of the constituent members of larger inter-human collectives such as a society or state to each other and the group as a whole. My conviction is rooted in certain general presuppositions regarding the nature of the human and religion.